2018
DOI: 10.7717/peerj.6036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key candidate genes and biological pathways in bladder cancer

Abstract: BackgroundBladder cancer is a malignant tumor in the urinary system with high mortality and recurrence rates. However, the causes and recurrence mechanism of bladder cancer are not fully understood. In this study, we used integrated bioinformatics to screen for key genes associated with the development of bladder cancer and reveal their potential molecular mechanisms.MethodsThe , , and expression profiles were downloaded from the Gene Expression Omnibus database, and these datasets contain 304 tissue samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 58 publications
7
71
0
Order By: Relevance
“…24 Several previously publications have uncovered that TOP2A is a poor prognostic biomarker in BCa. [25][26][27] In addition, Zeng et al 28 In conclusion, our study revealed that the prognostic model based on comprehensive study including WGCNA, DEGs screening and LASSO Cox regression has reliable reproducibility and accuracy in predicting prognosis of BCa and even pan-cancer.…”
Section: Discussionmentioning
confidence: 54%
“…24 Several previously publications have uncovered that TOP2A is a poor prognostic biomarker in BCa. [25][26][27] In addition, Zeng et al 28 In conclusion, our study revealed that the prognostic model based on comprehensive study including WGCNA, DEGs screening and LASSO Cox regression has reliable reproducibility and accuracy in predicting prognosis of BCa and even pan-cancer.…”
Section: Discussionmentioning
confidence: 54%
“…Microarray analysis is a new method to study tumor genes, search for molecular targets of tumor drug therapy and monitor prognosis. However, due to the heterogeneity of the experimental samples, different detection platforms and data processing methods generate inconsistent results [3]. The study was based on biological information in the GEO database, and the final results were obtained by analyzing the molecular functions of mRNA associated with thyroid cancer and the signal pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the morbidity of bladder urothelial carcinoma has increased, and the recurrence rate is high. Nonmuscle‐invasive bladder urothelial carcinoma (NMIBC) accounts for approximately 75% of bladder urothelial carcinoma, and approximately 80% of NMIBC patients relapse within 5 years after initial treatment . The invasion and metastasis of bladder urothelial carcinoma are important causes of recurrence and death from bladder urothelial carcinoma .…”
Section: Introductionmentioning
confidence: 99%